Inefficiency in irish agriculture - Leddin, A (Economic & Social Studies, 1980)
The purpose of this paper is to compare the relative efficiency of two similar groups of farms in Irish agriculture. Using a restricted profit function to measure economic efficiency and both of its components, price efficiency and technical efficiency, it was found that differences in the behaviour of farm groups do exist and that both failed to maximise profits. The implications for achieving increases in the growth rate of agricultural output are noted.
Keywords: Economics; Sociology